Relevance of G-quadruplex structures to pharmacogenetics - Cree, Simone L.; Kennedy, Martin A. (Frontiers in Pharmacology, 2014)
G-quadruplexes are non-canonical secondary structures formed within nucleic acids that are involved in modulating cellular processes such as replication, gene regulation, recombination and epigenetics. Within genes, there is mounting evidence of G-quadruplex involvement in transcriptional and post transcriptional regulation. We report the presence of potential G-quadruplex motifs within relevant sites of some important pharmacogenes and discuss the possible implications of this on the function and expression of these genes. Appreciating the location and potential functions of these motifs may be of value when considering the impacts of some pharmacogenetic variants. G-quadruplexes are also the focus of drug development efforts in oncology and we highlight the broader pharmacological implications of treatment strategies that may target G-quadruplexes.